Late Paleozoic Evolution of the Anadarko Basin: Implications for Laurentian Tectonics and the Assembly of Pangea. Issue 10 (21st October 2022) - Hobbs, Noah. F.; van Wijk, Jolante W.; Leary, Ryan; Axen, Gary J.
Abstract: Interplay between marginal and intraplate late Paleozoic tectonics in southeastern Laurentia is a subject of debate. In southern Laurentia, intraplate deformation has been attributed to combinations of compressive forces from orogenic belts in the west, southwest, and southeast. While left‐lateral transpression is generally an accepted mechanism for formation of uplifts in the Southern Oklahoma Aulacogen (SOA), to date no studies have explained the driving mechanisms of these kinematics. Here, we analyze the Southern Oklahoma Transpressional System (SOTS), a ∼500 km long ∼50 km wide fault zone that extends from the southeastern Laurentian margin into the plate interior along Cambrian lithospheric weaknesses inherited from the SOA. We use a compilation of published studies to present detailed, time‐integrated sedimentary thickness maps of SOTS‐related basins. We combine these maps with a new interpretation of three 2D seismic reflection lines to constrain timing and kinematics of all major late Paleozoic SOTS fault zones. We show that the SOTS kinematics evolved from contraction to left‐lateral strike‐slip during Mississippian‐Pennsylvanian time. Tectonic activity and fault kinematics in the SOTS are explained by a model in which a remnant ocean basin closed diachronously from northeast to southwest along the Southern Appalachian and Ouachita‐Marathon orogens. Left‐lateral transpression during diachronous closure of the Rheic oceanic basin along the Ouachita‐Marathon margin is related to rotation of the stress field due to changes in slab‐pull and eastward drift of Laurentia toward Gondwana. We speculate that the SOTS acted in part as a STEP (subduction‐transfer edge propagator) fault that followed the pre‐existing SOA. Key Points: Slab‐driven tectonics along the SE Laurentian margin Southern Oklahoma Transpression System links marginal and intraplate deformation late Paleozoic kinematics change from oblique convergence to left‐lateral strike‐slip in the Southern Oklahoma Transpression System